FREIGHTVISION - Sustainable European Freight Transport 2050 Forecast, Vision and Policy Recommendation - Helmreich, Stephan; Keller, Hartmut; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book has been written on the basis of the research done between 2008 and 2010 as part of the European Commission funded FREIGHTVISION project. The (3z(BFREIGHTVISION - Freight Transport 2050 Foresight(3y (Bproject was funded by the Directorate General MOVE to design a long term vision for European freight transport in 2050 and to identify actions and research to progress appropriate freight transport measures in Europe. The project was carried out as a foresight process encompassing four conferences in which the project team identified and developed with the aid of more than 100 experts an action plan for securing long term freight transport in Europe. The book provides insights into the freight transport visions and Backcasts identified for 2035 and 2050, issues which need to be addressed and measures which were assessed to be part of future paths to assure an economical, environmental, and social freight transport system.s
Part 1: Introduction and Approach -- Part 2: Methods -- Foresight Process -- Model for calculating long distance freight emissions and energy consumption -- TRANS-TOOLS -- Part 3: Analysis -- External Factors -- Forecast -- Vision -- Scenario -- Part 4: Recommendation -- Policy Actions -- Action Plan and Conclusions -- Appendices -- Index.
Keywords: Engineering; Engineering economy; Sustainable development; Regional economics; Engineering; Engineering Economics, Organization, Logistics, Marketing; Sustainable Development; Regional/Spatial Science